Scented grasses in Norway - Identity and uses - Alm, Torbjørn (Journal of Ethnobiology and Ethnomedicine, 2015)
Published version. Source at http://doi.org/10.1186/s13002-015-0070-y . Background: Some grass species are richer in coumarin and thus more sweetly scented than others. These have been eagerly sought after in parts of Norway, but the tradition has been weakly documented, both in terms of the species collected, their vernacular names, and uses. Methods: Based on literature data and a substantial body of information collected during my own ethnobotanical field work, artefacts and voucher specimens, the grass species are identified, and their uses clarified. Results: In Norwegian literature, the tradition of collecting and using scented grasses has received little attention, and past authors largely refer it to Anthoxanthum spp. The tradition’s concentration to the Sámi strongholds of northernmost Norway, and most authors’ lacking knowledge of the Sámi language, have contributed to the weak and misleading coverage in previous publications. Coumarin-rich grass species are well known in folk tradition in northernmost Norway, as luktegress (Norwegian, “scent grass”), háissasuoidni (North Sámi, “scent grass”), hajuheinä (Finnish, “scent grass”), or similar terms. They have been (and still are) frequently collected, and used as perfume, for storing with clothes, and a number of other purposes. Despite literature records identifying the species used as Anthoxanthum odoratum coll. (including A. nipponicum), the main source utilized in North Norway is Hierochloë odorata, both ssp. arctica and ssp. odorata. Anthoxanthum nipponicum and Milium effusum are alternative, but infrequently used sources of material, depending on local tradition and availability. Conclusion: By far the most important grass species hiding behind the “scented grass” tradition in Norway is Hierochloë odorata. Anthoxanthum nipponicum is also used, but much less frequently, and only a single record confirms the use of Milium effusum. Only the foliage of Hierochloë provides suitable material for making traditional braids. The three major ethnic groups ...